Optimizing The Literacy Corner To Increase Maritime Cultural Knowledge In Galesong Baru Village: Optimalisasi Pojok Literasi untuk Meningkatkan Pengetahuan Budaya Bahari di Desa Galesong Baru - Khaerunnisa; Ahmad Subair; Nur Amalia (Gudang Jurnal Pengabdian Masyarakat, 2024)
This community service program aimed to enhance maritime cultural knowledge in Galesong Baru Village through the optimization of the Literacy Corner. Galesong Baru, known for its rich maritime heritage, faces challenges in preserving local knowledge and traditions amidst social changes and modernization. To address this issue, the program involved renovating the Literacy Corner, adding relevant educational materials, and conducting various educational activities. These activities included reading sessions, discussions, and workshops focused on maritime culture, as well as involving maritime experts and local leaders to provide in-depth insights. Program evaluation showed a significant increase in maritime cultural knowledge among participants, particularly among the younger generation. Pre- and post-program surveys indicated substantial improvement in understanding maritime traditions, such as boat-making and fishing techniques. The optimized Literacy Corner has become a more active hub, with increased visitation from the community. Support from the village government, local schools, non-governmental organizations, and the local community was crucial to the program's success. This program demonstrates that a participatory and collaborative approach in developing literacy centers can effectively enhance cultural knowledge and engage the community in preserving local heritage. The results of this program are expected to serve as a model for other coastal villages facing similar challenges in cultural preservation